High-entropy alloy catalyst as well as preparation method and application thereof

By using a high-entropy alloy catalyst, including five metal elements: Pt, W, Ni, Co, and Cu, the existing catalysts have been solved, with high cost, insufficient activity, easy CO poisoning, poor stability and long preparation time, and an efficient, stable and low-cost methanol oxidation reaction is achieved.

CN119542446APending Publication Date: 2025-02-28TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411716813.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing methanol oxidation catalysts have high cost, insufficient activity, easy to be poisoned by CO, poor stability, and long preparation time, and the preparation process is cumbersome.

Method used

A high-entropy alloy catalyst is used, including five metal elements: Pt, W, Ni, Co, and Cu, and is prepared as a carbon support. It is prepared by ultrasonic spray atomization technology and thermal decomposition and reduction method. The metal particle size is less than 10nm.

Benefits of technology

The electrochemical active area of ​​the catalyst is improved, the catalyst cost is reduced, the stability and reusability are enhanced, and the efficiency and rate of methanol oxidation reaction are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the technical field of methanol oxidation reaction, and particularly relates to a high-entropy alloy catalyst as well as a preparation method and application thereof. The catalyst takes carbon as a carrier and comprises five metal elements, namely Pt, W, Ni, Co and Cu, and the five metal elements are marked as PtWNiCoCu / C-x. The preparation method of the high-entropy alloy catalyst comprises the following steps that S1, a carbon carrier is dispersed in a solvent, ultrasonic treatment is conducted for 30 min, then precursor solutions are added into the solvent, the precursor solutions are salt solutions of five kinds of metal including Pt, W, Ni, Co and Cu, and then vacuum stirring is conducted for 0.5-2 h at the room temperature through a reduced pressure distillation rotary evaporator, so that metal precursors are evenly dispersed; and S2, atomizing the solution in the step S1 by an ultrasonic atomizer, carrying the atomized solution into a high-temperature reaction furnace by carrier gas, carrying out thermal decomposition reduction for 2 hours, and cooling to room temperature to obtain the catalyst PtWNiCoCu / C-x. Uniform distribution of the alloy on the carbon carrier is effectively promoted through ultrasonic atomization, and the obtained high-entropy alloy is small in particle size, large in specific surface area and excellent in electrical property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of methanol oxidation reaction, and in particular relates to a high entropy alloy catalyst and a preparation method and application thereof. Background Art

[0002] Direct methanol fuel cells (DMFCs) are energy conversion devices with high energy density and power density. Their low operating temperature and simple fuel processing make them popular in portable devices and small electronic products. However, due to the relatively slow oxidation reaction of methanol in DMFCs and the poor long-term stability of the catalyst, efficient catalysts are needed to accelerate the reaction rate and improve the overall performance of the oxidation reaction. Currently, Pt is one of the most effective anode catalysts for methanol oxidation reaction (MOR) in DMFCs, but its application is limited by its high cost, insufficient activity, easy CO poisoning and poor stability. To address these problems, researchers are committed to alloying Pt with other elements. This strategy effectively adjusts the structure and electronic properties of Pt. Traditional alloy design usually focuses on using only one or two metal elements, which limits the development potential of Pt-based alloys. In recent years, high-entropy alloys have attracted widespread attention due to their excellent mechanical properties, corrosion resistance and thermal stability.

[0003] High entropy alloys, formed by the fusion of at least five metal elements, exhibit four significant characteristics: high entropy effect, lattice distortion effect, hysteresis diffusion effect and unique "cocktail effect". These effects work together to give high entropy alloys excellent stability and adjustable catalytic activity. In particular, in terms of electrochemical properties, the combined action of multiple metal elements can significantly enhance their catalytic activity, showing extraordinary performance optimization potential. Patent CN116574957A discloses a high entropy alloy and its preparation method, membrane electrode assembly and fuel cell. The preparation method of high entropy alloy is cumbersome and lengthy, that is, stirring redox reaction under a protective atmosphere of surfactant, reducing agent, solvent and at least one of nitrogen and inert gas, and the synthesis of high entropy alloy catalyst must first use PdPtCu nanosheets as seeds, and the total time exceeds 22h to obtain PdPtCuPbBiUNRs / C. Summary of the invention

[0004] The present invention aims to provide a high entropy alloy catalyst and a preparation method and application thereof, so as to solve the problems of high cost, insufficient activity, CO poisoning, poor stability, long preparation time and complicated preparation process of the current methanol oxidation catalyst.

[0005] In order to achieve the above object, the present invention adopts the following technical scheme: A high entropy alloy catalyst, with carbon as a carrier, contains five metal elements, namely Pt, W, Ni, Co and Cu, and is denoted as PtWNiCoCu / Cx.

[0006] Preferably, the size of the metal particles in the high entropy alloy catalyst is less than 10 nm.

[0007] The preparation method of the high entropy alloy catalyst comprises the following steps: S1: The carbon carrier is dispersed in a solvent, and after ultrasonic treatment for 30 minutes, the precursor solution is added to the solvent respectively. The precursor solution is a salt solution of five metals: Pt, W, Ni, Co, and Cu. The liquid is then stirred in vacuum at room temperature using a reduced pressure distillation rotary evaporator for 0.5 to 2 hours to make the metal precursors evenly dispersed; S2: The S1 solution was atomized by an ultrasonic atomizer and then carried into a high-temperature reactor by a carrier gas for 2 hours of thermal decomposition and reduction. The catalyst PtWNiCoCu / Cx was obtained after cooling to room temperature.

[0008] Preferably, in step S1, the carbon carrier is selected from Ketjen black or XC-72 conductive carbon black.

[0009] Preferably, the solvent in step S1 is anhydrous ethanol or ethylene glycol, and the salt solutions of the five metals are one or more of chlorides, nitrates, and sulfates.

[0010] Preferably, the molar content of each metal element in step S1 accounts for 18% to 22% of the total metal molar content.

[0011] Preferably, in step S2, the carrier gas is a hydrogen-argon mixture, with the hydrogen accounting for 10% to 20%.

[0012] Preferably, the carrier gas inlet speed in step S2 is 5-10 L / min, and the thermal decomposition reduction temperature is 500-800°C.

[0013] Preferably, in the step S2, the metal in the catalyst PtWNiCoCu / Cx accounts for 20% of the total mass.

[0014] The application of the high entropy alloy catalyst is used for the electrocatalytic oxidation of methanol as an electrocatalyst for the anode reaction of a direct methanol fuel cell. The specific steps of the application are: Preparation of working electrode: Weigh 2 mg of the catalyst prepared by the present invention and add 970 μL of a mixture of anhydrous ethanol and water (anhydrous ethanol: water = 1:3) and 30 μL of Nafion solution (5 wt%) in sequence, and ultrasonicate the slurry in an ice-water bath for 1 h to obtain catalyst ink, then transfer 10 μL and drop-coat it on a treated glassy carbon rotating disk electrode (d = 5 mm). After the drop-coating is completed, dry it at room temperature to obtain a working electrode.

[0015] The electrochemical performance tests were all carried out on a Princeton electrochemical workstation PMC1000 at room temperature. The test system was a standard three-electrode system, in which the Hg / HgO electrode and platinum mesh (1.5*1.5 cm) were the reference electrode and the counter electrode, respectively, and the rotating disk electrode coated with a catalyst was the working electrode. Before the methanol oxidation test, the three-electrode system was saturated with high-purity N2 to exclude the dissolved oxygen in the electrolyte.

[0016] Cyclic voltammetry (CV): The test scan range is 0.05~1.05V (vs. RHE), and the scan rate is 50mV·s -1 .

[0017] CO stripping test: the test scan range is 0.05~1.05V (vs.RHE), and the scan rate is 50mV·s -1 .

[0018] Chronoamperometric test (IT): The test parameters were set to a constant potential of 0.6 V (vs. RHE) and a test time of 20,000 s.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) The preparation method of the invention uses ultrasonic spray atomization technology to carefully control the uniform distribution of the alloy on the carbon carrier to avoid the occurrence of agglomeration. The morphology of the high-entropy alloy prepared by the spray pyrolysis method is easy to control to be a regular spherical shape with uniform particle size (less than 10nm). In addition, this preparation method makes the catalyst have a high electrochemical active area (95.98m 2 ·g -1 Pt ), so that it exposes more active sites, increases the contact area with the reactants, has high activity, and improves the efficiency and rate of the reaction; (2) The spray pyrolysis method does not require filtering, washing, drying, or crushing, and has a short preparation time, a simple preparation process, high production efficiency, and universal applicability. It only uses anhydrous ethanol or ethylene glycol as a solvent, does not require the addition of any reducing agent, is environmentally friendly, prevents CO poisoning, and meets the requirements of sustainable development. (3) The present invention uses a variety of non-precious metals to replace the traditional Pt precious metal, which greatly reduces the amount of precious metal Pt used and reduces the catalyst cost; at the same time, the combination of multiple elements makes the high entropy alloy have a controllable electronic structure, further improving its electrochemical activity; (4) The five metals form a single-phase high-entropy compound. The disordered chemical composition and lattice distortion significantly slow down the diffusion rate of the metal elements, further improving the stability and reusability of the catalyst, and providing a new idea for optimizing catalyst performance. (5) The high entropy alloy catalyst of this invention was first used in the direct methanol oxidation reaction anode methanol reaction and showed excellent electrocatalytic activity (6.4Amg -1 Pt @0.8VVs.RHE), this performance not only surpasses the best commercial platinum-carbon catalyst currently available, but also provides new directions and ideas for the research and application of electrocatalytic methanol oxidation catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The XRD patterns of Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 are shown; Figure 2 TEM image of Example 2; Figure 3 For Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 MKOH electrolyte, the scan rate is 50 mV·s -1 Cyclic voltammogram measured at room temperature. Figure 4 For Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 M KOH + 1 M CH3OH electrolyte, the scan rate is 50 mV·s -1 Cyclic voltammogram measured at room temperature. Figure 5 For Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 MKOH electrolyte, the scan rate is 50 mV·s -1 CO stripping diagram measured at room temperature; Figure 6 The chronoamperometric curves of Example 1, Example 2, Example 3, Example 4, Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 M KOH + 1 M CH3OH electrolyte for 20000 s are shown. DETAILED DESCRIPTION

[0021] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and embodiments. Example 1

[0022] The preparation method of PtWNiCoCu / C-500 catalyst is as follows: S1: 30.08 mg of conductive carbon black was dispersed in 100 mL of ethylene glycol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate, 7.9 mg of tungsten hexachloride, 4.8 mg of nickel nitrate hexahydrate, 4.8 mg of cobalt nitrate hexahydrate, and 2.7 mg of copper nitrate trihydrate were added to the solution respectively, and then vacuum stirred for 2 h at room temperature using a reduced pressure distillation rotary evaporator; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 500°C for 2 h. After cooling to room temperature, the catalyst PtWNiCoCu / C-500 was obtained. Example 2

[0023] The preparation method of PtWNiCoCu / C-600 catalyst is as follows: S1: 30.08 mg of conductive carbon black was dispersed in 100 mL of anhydrous ethanol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate, 7.9 mg of tungsten hexachloride, 4.8 mg of nickel chloride hexahydrate, 4.8 mg of cobalt chloride hexahydrate, and 2.7 mg of cupric chloride dihydrate were added to the solution respectively, and then vacuum stirred for 2 h using a reduced pressure distillation rotary evaporator at room temperature; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 600°C for 2 h. After cooling to room temperature, the catalyst PtWNiCoCu / C-600 was obtained. Example 3

[0024] The preparation method of PtWNiCoCu / C-700 catalyst is as follows: S1: 30.08 mg of conductive carbon black was dispersed in 100 mL of anhydrous ethanol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate, 7.9 mg of tungsten hexachloride, 4.8 mg of nickel chloride hexahydrate, 4.8 mg of cobalt chloride hexahydrate, and 2.7 mg of cupric chloride dihydrate were added to the solution respectively, and then vacuum stirred for 2 h using a reduced pressure distillation rotary evaporator at room temperature; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 700°C for 2 h. After cooling to room temperature, the catalyst PtWNiCoCu / C-700 was obtained. Example 4

[0025] The preparation method of PtWNiCoCu / C-800 catalyst is as follows: S1: 30.08 mg of conductive carbon black was dispersed in 100 mL of anhydrous ethanol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate, 7.9 mg of tungsten hexachloride, 4.8 mg of nickel nitrate hexahydrate, 4.8 mg of cobalt nitrate hexahydrate, and 2.7 mg of copper nitrate trihydrate were added to the solution respectively, and then vacuum stirred for 2 h using a reduced pressure distillation rotary evaporator at room temperature; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 800°C for 2 h. After cooling to room temperature, the catalyst PtWNiCoCu / C-800 was obtained.

[0026] Comparative Example 1 The preparation method of PtW / C-600 catalyst is as follows S1: 30.32 mg of conductive carbon black was dispersed in 100 mL of ethylene glycol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate and 7.9 mg of tungsten hexachloride were added to the solution respectively, and then vacuum stirred for 2 h using a reduced pressure distillation rotary evaporator at room temperature; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 600°C for 2 h. After cooling to room temperature, the catalyst PtW / C-600 was obtained.

[0027] Comparative Example 2 The preparation method of PtNiCoCu / C-600 catalyst is as follows S1: 30.08 mg of conductive carbon black was dispersed in 100 mL of anhydrous ethanol solution. After ultrasonic treatment for 30 min, 10.4 mg of chloroplatinic acid hexahydrate, 4.8 mg of nickel chloride hexahydrate, 4.8 mg of cobalt chloride hexahydrate, and 2.7 mg of cupric chloride dihydrate were added to the solution respectively, and then vacuum stirred for 2 h using a reduced pressure distillation rotary evaporator at room temperature; S2: The S1 solution was atomized by an ultrasonic atomizer and then brought into a high-temperature reactor by a hydrogen-argon mixture at a flow rate of 5 L / min. The thermal decomposition reduction temperature was 600°C for 2 h. After cooling to room temperature, the catalyst PtNiCoCu / C-600 was obtained.

[0028] Comparative Example 3 Pt / C was purchased from commercial Pt / C (46.8 wt % Pt).

[0029] The catalyst prepared by the present invention was tested for its performance in electrocatalytic oxidation of methanol.

[0030] Preparation of working electrode: Weigh 2 mg of the catalyst prepared by the present invention and add 970 μL of a mixture of anhydrous ethanol and water (anhydrous ethanol: water = 1:3) and 30 μL of Nafion solution (5wt%) in sequence, and ultrasonicate the slurry in an ice-water bath for 1 h to obtain catalyst ink, then transfer 10 μL and drop-coat it on a treated glassy carbon rotating disk electrode (d = 5 mm). After the drop-coating is completed, dry it at room temperature to obtain a working electrode.

[0031] The electrochemical performance tests were all carried out on a Princeton electrochemical workstation PMC1000 at room temperature. The test system was a standard three-electrode system, in which the Hg / HgO electrode and platinum mesh (1.5*1.5cm) were the reference electrode and the counter electrode, respectively, and the rotating disk electrode coated with a catalyst was the working electrode. Before the methanol oxidation test, the three-electrode system was saturated with high-purity N2 to exclude the oxygen dissolved in the electrolyte.

[0032] Cyclic voltammetry (CV): The test scan range is 0.05~1.05V (vs. RHE), and the scan rate is 50mV·s -1 .

[0033] CO stripping test: the test scan range is 0.05~1.05V (vs.RHE), and the scan rate is 50mV·s -1 .

[0034] Chronoamperometric test (IT): The test parameters were set to a constant potential of 0.6 V (vs. RHE) and a test time of 20,000 s.

[0035] The catalyst prepared by the present invention is structurally characterized: Figure 1 The XRD patterns of Example 1, Example 2, Example 3, Example 4, Comparative Example 1 and Comparative Example 2 are shown in FIG. Figure 1 It can be seen that the catalyst PtWNiCoCu / Cx exhibits a typical face-centered cubic structure, and the peaks at 42.4° and 49.0° correspond to the (111) and (200) planes of the crystal Pt; in addition, compared with PtW / C-600, the positive shift of the Pt peak in the XRD spectrum indicates the formation of the PtWNiCoCu / Cx high entropy alloy, forming a single-phase solid solution. The weaker diffraction peaks in the XRD of PtWNiCoCu / C-500 may be due to the lower crystallinity caused by the lower thermal decomposition temperature. The wide and low diffraction peaks in the XRD of PtWNiCoCu / C-600 indicate that the high entropy alloy has the characteristics of small grain size and many defects. The higher XRD peak intensities of PtWNiCoCu / C-700 and PtWNiCoCu / C-800 indicate that they have relatively large particle sizes.

[0036] Figure 2 is the TEM image of Example 3, Figure 2 It shows that the PtWNiCoCu / C-600 high entropy alloy prepared by the present invention has the morphology of nanoparticles, and its particle size is less than 10nm.

[0037] Figure 3 (a) Figure 4(a) Example 1, Example 2, Example 3 and Example 4 in 1 M KOH electrolyte and 1 M KOH + 1 M CH3OH electrolyte, with a scan rate of 50 mV·s -1 Cyclic voltammogram measured at room temperature. Figure 3 (b) Figure 4 (b) Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 M KOH electrolyte and 1 M KOH + 1 M CH3OH electrolyte, with a scan rate of 50 mV·s -1 Cyclic voltammogram measured at room temperature. Figure 3 (a) Figure 3 (b) It can be seen that at low potential, both the example and comparative example catalysts exhibit typical H atom desorption peaks, and PtWNiCoCu / C-600 has a larger electrochemical active area. Figure 4 (a) Figure 4 (b) shows the CV test of methanol oxidation in a nitrogen-saturated alkaline solution. It can be seen from the figure that the catalyst shows clear anodic peaks in both the forward and reverse scans, corresponding to the oxidation of methanol and its intermediates, respectively. The mass activity is obtained by normalizing the current to the mass loading of Pt. Compared with Comparative Examples 1, 2 and 3, PtWNiCoCu / Cx shows enhanced mass activity and PtWNiCoCu / C-600 shows a higher mass activity of 6.4 Amg Pt -1 @0.8VVs.RHE.

[0038] Figure 5 (a) is a CO stripping diagram of Example 1, Example 2, Example 3 and Example 4 in 1 M KOH electrolyte. Figure 5 (b) is the CO stripping diagram of Comparative Example 1, Comparative Example 2 and Comparative Example 3 in 1 M KOH electrolyte. Figure 5 (a) It can be seen that the CO oxidation peak potentials of PtWNiCoCu / C-500, PtWNiCoCu / C-600, PtWNiCoCu / C-700, and PtWNiCoCu / C-800 are 685mV, 676mV, and 681mV, respectively. Figure 5(b) It can be seen that the CO oxidation peak potentials of PtNiCoCu / C-600, PtW / C-600, and Pt / C are 684mV, 683mV, 692mV, and 724mV, respectively. The CO oxidation peak voltage of PtWNiCoCu / Cx shows a negative shift compared with PtNiCoCu / C-600, PtW / C-600, and Pt / C, indicating that CO in PtWNiCoCu / Cx can be oxidized at a lower potential, reducing CO poisoning, and PtWNiCoCu / C-600 has a lower CO oxidation peak potential value corresponding to its mass activity.

[0039] Figure 6 (a) is the chronoamperometric curve of Example 1, Example 2, Example 3 and Example 4 in 1 M KOH + 1 M CH3OH electrolyte at a constant potential of 0.6 V (vs. RHE), Figure 6 (b) is the chronoamperometric curve of comparative examples 1, 2 and 3 in 1 MKOH+1 M CH3OH electrolyte at a constant potential of 0.6 V (vs. RHE). It can be seen from the figure that the rapid decrease in current density at the beginning is attributed to the adsorption of intermediate products on the Pt surface. As time goes by, the anode current density reaches a stable state, which may be due to the balance between the intermediate adsorption and oxidation rates. After 20,000 s, the current density of commercial Pt / C almost dropped to 0. PtWNiCoCu / Cx showed better long-term stability compared with PtNiCoCu / C-600, PtW / C-600 and Pt / C, and the PtWNiCoCu / C-600 catalyst had better stability, maintaining 52% of the initial catalytic activity.

[0040] The above are only preferred embodiments of the present invention. All equivalent structural changes made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the protection scope of the present invention.

Claims

1. A high entropy alloy catalyst, characterized in that: It uses carbon as a carrier and contains five metal elements: Pt, W, Ni, Co, and Cu, and is recorded as PtWNiCoCu / Cx.

2. A high entropy alloy catalyst according to claim 1, characterized in that: The size of metal particles in high entropy alloy catalysts is less than 10nm.

3. The method for preparing a high entropy alloy catalyst according to claim 1, characterized in that: The steps include: S1: The carbon carrier is dispersed in a solvent, and after ultrasonic treatment for 30 min, the precursor solution is added to the solvent respectively. The precursor solution is a salt solution of five metals: Pt, W, Ni, Co, and Cu. The liquid is then stirred in vacuum at room temperature using a reduced pressure distillation rotary evaporator for 0.5-2h to make the metal precursors evenly dispersed; S2: The S1 solution was atomized by an ultrasonic atomizer and then carried into a high-temperature reactor by a carrier gas for 2 hours of thermal decomposition and reduction. The catalyst PtWNiCoCu / Cx was obtained after cooling to room temperature.

4. The method for preparing a high entropy alloy catalyst according to claim 3, characterized in that: In the step S1, the carbon carrier is selected from Ketjen black or XC-72 conductive carbon black.

5. The method for preparing a high entropy alloy catalyst according to any one of claims 3 or 4, characterized in that: In step S1, the solvent is anhydrous ethanol or ethylene glycol, and the salt solutions of the five metals are one or more of chlorides, nitrates, and sulfates.

6. The method for preparing a high entropy alloy catalyst according to claim 5, characterized in that: The molar content of each metal element in step S1 accounts for 18% to 22% of the total metal molar content.

7. The method for preparing a high entropy alloy catalyst according to claim 6, characterized in that: In step S2, the carrier gas is a hydrogen-argon mixture, with the hydrogen accounting for 10% to 20%.

8. The method for preparing a high entropy alloy catalyst according to claim 7, characterized in that: The carrier gas inlet speed in step S2 is 5-10 L / min, and the thermal decomposition reduction temperature is 500-800°C.

9. The method for preparing a high entropy alloy catalyst according to claim 8, characterized in that: In the step S2, the metal in the catalyst PtWNiCoCu / Cx accounts for 20% of the total mass.

10. The use of a high entropy alloy catalyst according to claim 1, characterized in that: Used for methanol electrocatalytic oxidation, as an electrocatalyst for the anode reaction of direct methanol fuel cells, the specific application steps are: Preparation of working electrode: Weigh 2 mg of the catalyst prepared by the present invention and add 970 μL of a mixture of anhydrous ethanol and water (anhydrous ethanol: water = 1:3) and 30 μL of Nafion solution (5 wt%) in sequence, and ultrasonicate the slurry in an ice-water bath for 1 h to obtain catalyst ink; then transfer 10 μL to a drop coating on a treated glassy carbon rotating disk electrode (d = 5 mm), and dry at room temperature after the drop coating to obtain a working electrode.

Citation Information

Patent Citations

  • High-entropy alloy and preparation method thereof, membrane electrode assembly and fuel cell

    CN116574957A